Comparative evaluation of autologous platelet rich plasma and triamcinolone acetonide injection in the management of erosive lichen planus and oral submucous fibrosis: a clinical study - Sharma, Shubham; kamarthi, Nagaraju; Sumit Goel; Sangeeta Malik; Swati Gupta; Abhinav Sharma (International Journal of Basic & Clinical Pharmacology, 2023)
Background: It is need of an hour to establish an effective and efficient treatment modality for OLP and OSMF with lesser or no adverse effects. Platelet rich plasma can be used in mucosal lesions as it has a high concentration of various growth factors and anti-inflammatory properties. It could be a better novel substitute to the corticosteroid without any side effects. The present study is an effort to evaluate the therapeutic effects of intralesional injection of PRP in oral erosive lichen planus and OSMF compared to intralesional corticosteroids in the same patient. Methods: It was a randomized controlled clinical study consisting of 40 patients between the age groups of 18-60 years visiting dental OPD diagnosed clinically with either erosive lichen planus or OSMF. Triamcinolone 40 mg(1mg/ml) mixed with 2% (1:80,000) lignocaine hydrochloride was injected into the lesion on one side in case of erosive lichen planus and into the submucosal plane and fibrous bands in case of OSMF patients. Autologous PRP was prepared and injected on the other side in same patients. At every visit, all the patients were evaluated for pain and burning sensations, size, and severity of the lesion, and interincisal mouth opening (mm). The parameters were measured and recorded during the patient’s every visit. All the results were obtained and statically analyzed. Results: Intralesional injections of triamcinolone acetonide and PRP are effective in reducing pain and burning sensation in OSMF, but PRP is less effective in improving cheek flexibility as compared to triamcinolone acetonide. In OLP, both triamcinolone acetonide and PRP are almost equally effective in reducing the size of the lesion. However, PRP shows slightly better results in reducing the severity of the lesion and in pain and burning sensation in the patients of OLP as compared to intralesional triamcinolone acetonide. Conclusions: Thus, PRP is an effective modality in treating both OSMF and oral erosive lichen planus with no adverse effects.